Digital pervasiveness and divisiveness: the role of an African government in enabling healthy digital futures - Bashir, Iman; Oyewale, Fisayo (University of the Witwatersrand, Johannesburg, 2023)
Africa has been said to be left behind during the past industrial revolutions. In the face of the fourth industrial revolution, in which digitalisation plays a key role, technology is seen as pervasive (according to African digital futures), especially in its cross-sectorial application and everyday use. The use of digital tools and applications remains driven by growing interconnection, intelligent automation and interoperability, which continue to influence digital innovations and divides. Studies revealed disparity in the statistics regarding mobile internet connectivity for the already connected, coverage and the usage gap. The coverage gap was most pronounced, further widening the digital divide beyond location and affordability. Without addressing the issues of access, affordability and regulation, existing inequalities, digital vulnerabilities, political and ethnic divides escalate further. Research has also shown that open data in the continent contributes to government transparency, accountability and public innovation. However, few open data initiatives actively promote inclusion and equity. This research explores the diverse perspectives of digital age themes, alongside the opportunities, risks, paradoxes and techno-determinism, to analyse the efforts of African governments to digitally transform the continent. This paper further builds on the African digital governance project, which explored the value of data, ownership, policy and digitally enabled political participation. This essay explores the continent's ability for collective transformation, using the 5D model of appreciative inquiry, and suggests several points of view for escaping the status quo.
Keywords: African Governance; Digital Age; Digital pervasiveness; Futures; Data; Diversity and inclusion; Governance; SDG-9: Industry, innovation and infrastructure